2016
DOI: 10.1186/s12888-016-0921-7
|View full text |Cite
|
Sign up to set email alerts
|

Results of a pilot cluster randomised trial of the use of a Medication Review Tool for people taking antipsychotic medication

Abstract: BackgroundGovernment policy encourages increasing involvement of patients in their long-term care. This paper describes the development and pilot evaluation of a ‘Medication Review Tool’ designed to assist people to participate more effectively in discussions about antipsychotic drug treatment.MethodsThe Medication Review Tool developed consisted of a form to help patients identify pros and cons of their current antipsychotic treatment and any desired changes. It was associated with a website containing inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 26 publications
1
73
0
Order By: Relevance
“…Clinicians have been found to underestimate the impact of the adverse effects of neuroleptics on patients' quality of life [66,67], which may contribute to the difficulties of achieving a more collaborative approach to decision-making with people with severe mental disorders [65,68]. A fuller understanding of how neuroleptic drugs impact on important aspects of people's experience and feelings about themselves, and how these effects are entwined with effects on symptoms will enable clinicians to better recognise and respond to patients' concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have been found to underestimate the impact of the adverse effects of neuroleptics on patients' quality of life [66,67], which may contribute to the difficulties of achieving a more collaborative approach to decision-making with people with severe mental disorders [65,68]. A fuller understanding of how neuroleptic drugs impact on important aspects of people's experience and feelings about themselves, and how these effects are entwined with effects on symptoms will enable clinicians to better recognise and respond to patients' concerns.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Four studies were cluster RCTs (n = 712 participants) 23 , 24 , 25 , 26 , 27 and the remaining 22 were before-after study designs (n = 7844 participants). 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 Studies were conducted in North America (15 studies), 28 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 39 , 42 , 43 , 46 , 47 , 48 , 49 Europe (10 studies) 23 , 25 , 26 , 27 , 29 , 38 , 40 , 41 , 44 , 45 and Australasia (1 study). 34 A total of 19 studies 23 , 26 , 27 , 28 ,…”
Section: Resultsmentioning
confidence: 99%
“…The first was one-off medication review, usually undertaken by a single professional and including a single class of psychotropic drug. 23 , 25 , 38 , 40 , 41 , 42 , 43 , 44 , 45 The second model was a longitudinal program of regular medication review, often by a multidisciplinary team who reviewed the participant’s psychotropic drug regimen in a series of meetings. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 The third type of focused psychotropic medication review was 2-stage, in which those at high risk of suboptimal drug therapy were identified using a rule applied to the electronic patient record and then directed to clinician medication review.…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for not recruiting people who were referred to the research team were noted. As this was a feasibility study, a formal sample size calculation was not performed but our a priori estimate was that 100 people with ID would be recruited based on previous feasibility studies that have trialled similar interventions in community settings 14…”
Section: Methodsmentioning
confidence: 99%